2013
DOI: 10.1016/j.jsp.2013.09.003
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of conjoint behavioral consultation on parents and children in the home setting: Results of a randomized controlled trial

Abstract: The present study is a large-scale randomized trial testing the effects of a family-school partnership model (i.e., Conjoint Behavioral Consultation, CBC) for promoting behavioral competence and decreasing problem behaviors of children identified by their teachers as disruptive. CBC is a structured approach to problem solving that involves consultants, parents, and teachers. The effects of CBC on family variables that are commonly associated with important outcomes among school-aged children (i.e., family invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 115 publications
(74 citation statements)
references
References 63 publications
4
67
0
3
Order By: Relevance
“…Given the goal-directed focus of CBC casework and emphasis on supporting the development of prosocial behaviors, it is not surprising to see significantly different outcomes across groups on social and adaptive skills but not externalizing and internalizing problems. It is noteworthy that these results generally corroborate and extend a previous RCT examining CBC efficacy in urban/suburban communities Sheridan et al, 2013), which found significant Time × Condition interactions for teacher and parent reports of social skills and teacher (but not parent) report of adaptive skills, but not externalizing or internalizing behaviors.…”
Section: Main Findingssupporting
confidence: 86%
See 3 more Smart Citations
“…Given the goal-directed focus of CBC casework and emphasis on supporting the development of prosocial behaviors, it is not surprising to see significantly different outcomes across groups on social and adaptive skills but not externalizing and internalizing problems. It is noteworthy that these results generally corroborate and extend a previous RCT examining CBC efficacy in urban/suburban communities Sheridan et al, 2013), which found significant Time × Condition interactions for teacher and parent reports of social skills and teacher (but not parent) report of adaptive skills, but not externalizing or internalizing behaviors.…”
Section: Main Findingssupporting
confidence: 86%
“…CBC has shown to be effective for elementary-aged children in urban settings. Previous research has demonstrated that children who participate in CBC show decreased levels of externalizing behaviors (arguing, temper tantrums, noncompliance) and increased levels of positive social and adaptive behaviors in the home and school settings Sheridan et al, 2013). Furthermore, parents who participate in the CBC process have reported more bi-directional communication with teachers and more positive, high quality relationships with their child's teacher (Sheridan, Clarke, Knoche, & Edwards, 2006;Sheridan et al, 2013).…”
Section: Overview Of Conjoint Behavioral Consultationmentioning
confidence: 99%
See 2 more Smart Citations
“…This disparity between fields may be due to key differences between general psychological or health support, which is often delivered directly to a client, and behavior analytic support which often involves training others in specific techniques (e.g., Deliperi et al 2015;Downs and Downs 2013;Wacker et al 2017) or using a more formal behavioral consultation model (see, for example, Sheridan et al 1996;Sheridan and Kratochwill 2007;Watson and Robinson 1996;Wilkinson 2006). These training and consultation approaches have been shown to be effective in enhancing consultee skills and fidelity (e.g., Collier-Meek and Sanetti 2014; Deliperi et al 2015;McKenney et al 2013) and improving child behavior or academic and social skills (e.g., Garbacz and McIntyre 2016;Sheridan et al 2006;Sheridan et al 2013;Wacker et al 2017). However, some authors highlight barriers to this type of support due to the amount of consultant time needed and difficulties providing training or behavioral consultation to clients in rural areas, suggesting that telehealth may be a useful alternative method of providing such support (e.g., Bice-Urbach and Kratochwill 2016; Fischer et al 2016a, b).…”
Section: Introductionmentioning
confidence: 99%